AsTeRICS, a flexible AT construction set. (3rd June 2014) - Ossmann, Roland; Parker, Stefan; Thaller, David; Pecyna, Karol; García‐Soler, Alvaro; Morales, Blanca; Weiß, Christoph; Veigl, Christoph; Kakousis, Konstantinos
SUMMARY A vast number of people with disabilities are supported by assistive technologies (AT). Often, AT solutions do not directly fit the specific requirements of a user, making costly adaptations necessary. Assistive Technology Rapid Integration & Construction Set (AsTeRICS) aims to change this situation by employing rapid prototyping technologies in AT. A construction set of building blocks to create flexible prototypes for each individual user is provided. This set is configured by a visual modelling software application which allows to connect all building blocks as needed, tailoring the prototype to the user's abilities and needs. Building blocks include sensors (which in this context includes not only stand‐alone sensors such as simple switch inputs but also vision systems, brain computer interfaces, and many more), data processing elements (mathematical and flow control), and actuators (such as mouse/keyboard replacement, smart environments, and mobile phone access). As central part of AsTeRICS, a runtime environment has been developed, handling all signal processing and data exchange operations needed for the interaction of the building blocks. Copyright © 2014 John Wiley & Sons, Ltd.